Artisan Women from San Antonio de Ibarra and their life experience - Chuquín Cadena, Andrea Paola (Revista Ecos de la Academia, 2023)
This article collects details of the dialogue with a group of artisans, from all spaces and social contexts belonging to San Antonio de Ibarra. The objective of this research is to study the case of women artisans in the sector, their contribution in the recognition of the quality of handicrafts and deepen their life experience. The research has a qualitative approach with a descriptive scope, applying semi-structured interviews to four women immersed in this trade and the representative of the "Madera de Mujeres" collective, as well as a record of the participation of the representatives in the "San Antuko" festival. organized by "Casa Durazno" on August 13, 2022, and the monitoring of the collective’s social networks. As a result, the trajectory and life experience in the female artisan production of the sector and the challenges they have faced as artisan women were evidenced. The most relevant result exposed that the woman was always immersed in the artisan work in an indirect way, being her desires to achieve visibility and the fair recognition of her work, this can be an opportunity to promote San Antonio de Ibarra.